Genome-wide identification of genes encoding cystathionine beta synthase domain-containing proteins in wheat and its relationship with anther male sterility under heat stress - Liu, Hongzhan; Wang, Qi; Xie, Liuyong; Xu, Kedong; Zhang, Fuli; Ruan, Xianle; Li, Lili; Tan, Guangxuan (Frontiers in Plant Science, 2022)
Cystathionine beta synthase (CBS) domains containing proteins (CDCPs) plays an important role in plant development through regulation of the thioredoxin system, as well as its ability to respond to biotic and abiotic stress conditions. Despite this, no systematic study has examined the wheat CBS gene family and its relation to high temperature-induced male sterility. In this study, 66 CBS family members were identified in the wheat genome, and their gene or protein sequences were used for subsequent analysis. The TaCBS gene family was found to be unevenly distributed on 21 chromosomes, and they were classified into four subgroups according to their gene structure and phylogeny. The results of collinearity analysis showed that there were 25 shared orthologous genes between wheat, rice and Brachypodium distachyon, and one shared orthologous gene between wheat, millet and barley. The cis-regulatory elements of the TaCBS were related to JA, IAA, MYB, etc. GO and KEGG pathway analysis identified these TaCBS genes to be associated with pollination, reproduction, and signaling and cellular processes, respectively. A heatmap of wheat plants based on transcriptome data showed that TaCBS genes were expressed to a higher extent in spikelets relative to other tissues. In addition, 29 putative tae-miRNAs were identified, targeting 41 TaCBS genes. Moreover, qRT-PCR validation of six TaCBS genes indicated their critical role in anther development, as five of them were expressed at lower levels in heat-stressed male sterile anthers than in Normal anthers. Together with anther phenotypes, paraffin sections, starch potassium iodide staining, and qRT-PCR data, we hypothesized that the TaCBS gene has a very important connection with the heat-stressed sterility process in wheat, and these data provide a basis for further insight into their relationship.